2019
DOI: 10.1021/acsomega.9b01465
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Mannose “Click” Conjugation to Polymeric Nanoparticles for Targeted siRNA Delivery to Human and Murine Macrophages

Abstract: “Smart”, dual pH-responsive, and endosomolytic polymeric nanoparticles have demonstrated great potential for localized drug delivery, especially for siRNA delivery to the cytoplasm of cells. However, targeted delivery to a specific cell phenotype requires an additional level of functionality. Copper-catalyzed azide–alkyne cycloaddition (CuAAC) is a highly selective bioconjugation reaction that can be performed in conjunction with other polymerization techniques without adversely affecting reaction kinetics, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Previous studies from our group have shown that increasing canonical NF-κB activity in macrophages is associated with a shift away from the M2 pro-tumor phenotype [23,24]. We therefore used immunofluorescence analysis to examine whether the anti-tumor effects observed in IKFM mice were accompanied by reduced M2 polarization of TAMs.…”
Section: In Established Ovarian Tumors Activation Of Nf-κb In Macropmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies from our group have shown that increasing canonical NF-κB activity in macrophages is associated with a shift away from the M2 pro-tumor phenotype [23,24]. We therefore used immunofluorescence analysis to examine whether the anti-tumor effects observed in IKFM mice were accompanied by reduced M2 polarization of TAMs.…”
Section: In Established Ovarian Tumors Activation Of Nf-κb In Macropmentioning
confidence: 99%
“…Although one study found that inhibition of canonical NF-κB signaling in TAMs leads to the anti-tumorigenic M1 phenotype [22], an increasing body of literature demonstrates the opposite, finding that increased NF-κB activity in macrophages polarizes them towards an M1-like anti-tumorigenic phenotype. We have shown that knockdown of cytoplasmic IκBα, inhibitor of NF-κB, promotes a shift towards the M1 phenotype and induces cytotoxicity towards tumor cells in cultured macrophages [23,24]. Moreover, complementary in vivo studies in transgenic mice overexpressing a constitutively activated form of cytoplasmic IKK2 specifically in macrophages, termed IKFM, show reduced growth and metastatic seeding of injected melanoma and mammary tumor cells [19,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These reaction conditions bypass potential toxicity associated with copper catalysis, which has been employed in many similar efforts to functionalise nanoparticles via alkyne-azide cycloaddition. [17][18][19] Characterisation of these nanoparticles revealed a marginal increase in diameter versus the nude azide NP control and a protein content of 16.1 ± 1.5 µg mg −1 polymer, indicating that conjugation had been achieved (Table 1).…”
Section: Nanoparticle Formulation and Characterisationmentioning
confidence: 99%
“…[ 10 ] It is shown to bind various carbohydrates and oligosaccharides, in particular, mannose either in a free form or conjugated to polymer scaffolds. [ 11 ] As of today, there is an extensive body of work using mannose as a targeting moiety to mannose macrophage receptor (MMR), in which various nanocarriers were employed for the delivery of small molecules, [ 12–16 ] proteins, [ 17,18 ] nucleic acids, [ 19–23 ] and structures like nanoparticles of different types [ 24–26 ] or supramolecular aggregates. [ 27 ] As far as the delivery of the plasmid DNA (pDNA) is concerned the most suitable vehicles are either lipoplexes or polyplexes.…”
Section: Introductionmentioning
confidence: 99%